Reduced Resting-State Functional Connectivity of the Somatosensory Cortex Predicts Psychopathological Symptoms in Women with Bulimia Nervosa - Lavagnino, Luca; Amianto, Federico; D’Agata, Federico; Huang, Zirui; Mortara, Paolo; Abbate-Daga, Giovanni; Marzola, Enrica; Spalatro, Angela; Fassino, Secondo; Northoff, Georg (Frontiers in Behavioral Neuroscience, 2014)
Background Alterations in the resting state functional connectivity (rs-FC) of several brain networks have been demonstrated in eating disorders. However, very few studies are currently available on brain network dysfunctions in bulimia nervosa (BN). The somatosensory network is central in processing body-related stimuli and it may be altered in BN. The present study therefore aimed to investigate rs-FC in the somatosensory network in bulimic women. Methods Sixteen medication-free women with BN (age=23±5 years) and 18 matched controls (age=23±3 years) underwent a functional magnetic resonance resting state scan and assessment of eating disorder symptoms. Within-network and seed-based functional connectivity analyses were conducted to assess rs-FC within the somatosensory network and to other areas of the brain. Results BN patients showed a decreased resting state functional connectivity both within the somatosensory network (t=9.0, df=1, P=0.005) and with posterior cingulate cortex (PCC) and two visual areas (the right middle occipital gyrus and the right cuneus)(P=0.05 corrected for multiple comparison). The region in the right middle occipital gyrus is implicated in body processing and is known as extrastriate body area, or EBA. The rs-FC of the left paracentral lobule with the EBA correlated with psychopathology measures like bulimia (r=-0.4; P=0.02) and interoceptive awareness (r=-0.4; P=0.01). Analyses were conducted using age, BMI (body mass index) and depressive symptoms as covariates. Conclusions Our findings show a specific alteration of the rs-FC of the somatosensory cortex in BN patients, which correlates with eating disorder symptoms. The connectivity between the somatosensory cortex and the EBA might be related to dysfunctions in body image processing. The results should be considered preliminary due to the small sample size.